Design fit in gamified online programming learning environment - Wang, Wei-Tsong; Sari, Mega Kartika (Learning and instruction, 2025)
The strategy for designing online programming learning through a gamified learning environment and its effects on learning outcomes remains a subject of debate. Using Task-Technology Fit (TTF) theory, this study investigates the impact of design fit on learning programming that supports game characteristics on learning outcomes. The technique of component-based structural equation modeling was used to examine the research hypotheses. Learning performance is influenced by cognitive load and student perception of TTF. Additionally, task complexity affects students' applicability of learning strategies and perceptions on TTF. The research findings can be used as guidelines for developing gamified online programming learning platforms by considering the features of the learning contexts to enhance students’ learning outcomes. •Attaining the fit of gamification design is critical to effective learning outcomes.•Task complexity and learning strategies are critical to design fit.•Task complexity indirectly affects design fit via learning strategies.•Cognitive load mediates the effect of TTF on learning performance.•Achieving design fit can enhance learning outcomes.